Łódź Jewish Society for Providing Care to Orphans and its Activities for Children and Young People during the World War I - Sosnowska, Joanna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
The origins of the Łódź Jewish Society for Providing Care to Orphans (Łódzkie Żydowskie Towarzystwo Opieki nad Sierotami – ŁŻTOS) date back to the period before the World War I and are related to the initiative of the Jewish community, which, in July 1907, applied to register a charitable organization aimed at providing aid to children and young people. The statute of the Society was drawn up. According to the statute, the Society was supposed to take care of the material, moral, and intellectual needs of Jewish orphans. The history of the Society is also related to the history of the Jewish family of Henryk and Zofia Hirszberg, as they were the founders of the building which became the offices of the Society just before the World War I and which was supposed to serve the orphans looked after by the organization. The Orphans’ Home, as that was the name of the centre for children and young people, was located in Łódź at Północna 38.
Keywords: orphans; Łódź; Jewish; charitable organizations